Marketing strategy for informal worker group in construction industry in Indonesia - Lukiyanto, Kukuh; Wijayaningtyas, Maranatha (MEC-J (Management and Economics Journal), 2017)
The paper aims to identify foreman’s strategies in marketing his/her group’s service as well as analyzes how the foreman finds a job in construction project. Qualitative method with phenomenological approach was used to address the research’s problem through a survey involving two project managers and four construction foremen. The paper provides the empirical insights about the marketing strategy applied by foreman as group leader in Indonesian construction industry. Foreman is regarded as an informal leader who has strong emotional and social ties with fellow workers. As the main liaison between management and labor, the foreman should be able to organize the work and labor to achieve project objectives. Management expects the foreman to be able to supply the needs of the labors of the construction projects, while the workers hope the foreman to be able to provide jobs for them regularly. Because of the chosen research approach, the research result may lack generalisability. In order to increase the generalisability, the researcher is encouraged to test the proposed hypothesis in the future research. The paper includes implications for the development of foremen’s role in marketing strategy and for fulfiling the balance between project manager’s and construction labours’ rights. This paper fulfils how marketing strategy applied by foremen can fulfil the project manager’s and the construction labours’ rights.Keywords: Foreman, construction workers, marketing strategy.